2021
DOI: 10.1093/icb/icab095
|View full text |Cite
|
Sign up to set email alerts
|

Video Recording and Analysis of Avian Movements and Behavior: Insights from Courtship Case Studies

Abstract: Video recordings are useful tools for advancing our understanding of animal movements and behaviour. Over the past decades, a burgeoning area of behavioural research has put forward innovative methods to investigate animal movement using video analysis, which include motion capture and machine learning algorithms. These tools are particularly valuable for the study of elaborate and complex motor behaviours, but can be challenging to use. We focus in particular on elaborate courtship displays, which commonly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…While the majority of camera trap research uses photographs, video footage may be more suitable for applications such as behavioural studies (Caravaggi et al., 2017; Janisch et al., 2021; Tagg et al., 2018), monitoring group size (Balestrieri et al., 2016; Green‐Barber & Old, 2018; Medeiros et al., 2019) or density estimation of unmarked species (Corlatti et al., 2020; Howe et al., 2017; Nakashima et al., 2018). Video footage may also increase public engagement and facilitate easier identification of species and individuals for citizen scientists (Reyes et al., 2017; Swinnen et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of camera trap research uses photographs, video footage may be more suitable for applications such as behavioural studies (Caravaggi et al., 2017; Janisch et al., 2021; Tagg et al., 2018), monitoring group size (Balestrieri et al., 2016; Green‐Barber & Old, 2018; Medeiros et al., 2019) or density estimation of unmarked species (Corlatti et al., 2020; Howe et al., 2017; Nakashima et al., 2018). Video footage may also increase public engagement and facilitate easier identification of species and individuals for citizen scientists (Reyes et al., 2017; Swinnen et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…First, camera traps can have slower trigger speeds and longer recovery times when set to video and therefore risk missing some events (Apps & McNutt, 2018; Findlay et al., 2020). Second, videos have larger file sizes, leading to faster filling of memory cards, and increased power consumption when recording, leading to shorter battery life (Blount et al., 2021; Janisch et al., 2021). A final concern is the longer processing time needed to view videos, which may be exacerbated by a lack of support for video management in software designed to streamline camera data management.…”
Section: Introductionmentioning
confidence: 99%
“…To convincingly suggest that immature males gain fitness benefits by subverting the mating decisions of females (by e.g., sneaking, stealing, or forcing copulations) researchers should genetically determine paternity among offspring. While accessing nests has proven challenging in birds of paradise (Frith & Beehler, 1998), better insight can be gained about the occurrence of alternative mating tactics in this taxon by monitoring banded populations and through the use of automated videos cameras placed at courts (Janisch et al., 2021). Intriguingly, rates of successful mountings by female‐plumaged birds appear to be comparable to those of adult males in our data set (Figure 2), suggesting that the species discussed in the present paper are promising models to study homosexual behaviour and alternative mating tactics.…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, we showed here that courtship calls and some of the visual display variables in our study population showed geographical variation consistent with micro-dialects, yet social proximity among male bowerbirds co-varied with signal similarity only for acoustic display components. Future studies should further focus on fine-scale parameters of visual displays, for example by means of motion capture techniques [44], to explore whether patterns of local variation may occur in postural components of visual displays.…”
Section: Discussionmentioning
confidence: 99%